Judo rules: searching for a wind of changes - Calmet, M.; Pierantozzi, E.; Sterkowicz, S.; Takito, M. Y.; Franchini, E. (International Journal of Performance Analysis in Sport, 2017)
After 2016, the International Judo Federation changed rules to promote the "positive" judo. This study compared two World Championships editions before and after the rules changes: Astana-2015 and Budapest-2017. Data from matches disputed in Astana (765) and Budapest (768) were analysed concerning: total match duration, frequency of scores and penalties, association between edition and extra-time, disqualifications and matches without penalties. Three-way ANOVA was used to compare sexes, weight categories and World Championships edition, with Fisher`s Least Significant Difference (LSD) test as post hoc. The associations between World Championships edition and matches finished in extra-time, disqualifications and matches without any score were tested via Chi-square. Results were: (a) no change in number of ippon when the same sex and weight category were considered across years; (b) number of waza-ari increased from Astana to Budapest; (c) number of penalties decreased from Astana to Budapest. Females in Budapest received less penalties than females in Astana and males in both competitions. Extra-lightweights received less penalties than lightweights upwards; heavyweights received more penalties than all other weight categories from middleweights downwards; (d) occurrence of extra-time and hansoku-make increased for females, males and all groups together; (e) males` matches were longer than females ones. Thus, the new rules partially achieved the goal proposed.